Are parents free to bestow their wealth onto their children? a juristic discourse on equality and justice in hibah - Awang, Abdul Bari; Awang Abd. Rahman @ Jusoh, Amilah (Universiti Malaya, 2014)
This study explores issues related to justice in the bestowal of gifts (hibah) by parents to their children. Hibah, in the current development, is practiced freely to the extent of being considered a favourite choice of transferring wealth. However, it is a potentially problematic practice because it opens up to preferential and unjust treatment. This paper aims to respond to some questions related to justice. How far does the principle of justice affect hibah? To which extent is it permissible to distribute property and wealth unequally among one’s children? What is the meaning of just distribution between male and female child? Are there special criteria prescribed that justify unequal distribution of hibah among children? These issues are discussed in reference to established views of classical as well as contemporary Muslim jurists.